ENHANCING ESL STUDENTS’ SPEAKING MOTIVATION THROUGH INSTAGRAM (IG) (Practitioner Research, 2022)
This study addresses the issue of investigating how Instagram (IG) helps to enhance students’ speaking skills in English, particularly their confidence and motivation in speaking. While many studies have looked at the impact of IG on language learning, little is known about Instagram could enhance ESL students’ communication skills. A qualitative case study was conducted which involved 6 students selected based on the purposive sampling technique, at one multi-ethnic secondary school in Petaling Jaya, Selangor. Multiple methods such as pre and post-interview sessions and IG postings were used to collect the data. Data were analyzed thematically and via content analysis. The findings revealed three themes associated with IG which are: Connecting, sharing and learning. IG also helped to enhance ESL students’ motivation and confidence in using English. It is recommended that language teachers implement media platform such as Instagram to create more conducive language learning environment. It also contributes to new ideas and knowledge on how teachers and learners can conceptualize and use Instagram in English speaking-lessons.